2010
DOI: 10.1210/jc.2009-2289
|View full text |Cite
|
Sign up to set email alerts
|

β-Cell Secretory Capacity and Demand in Recipients of Islet, Pancreas, and Kidney Transplants

Abstract: Impaired beta-cell secretory capacity in islet transplantation is best explained by a low engrafted beta-cell mass and not by a deleterious effect of tacrolimus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 42 publications
3
37
1
4
Order By: Relevance
“…Interestingly, the proinsulin/ C-peptide ratio is particularly elevated in islet transplant recipients who fail to maintain insulin independence (21)(22)(23), suggesting an association with graft failure. One study reported no difference in proinsulin/insulin ratio among islet transplant recipients, normal control subjects, and immunosuppressed recipients of other organ transplants in patients with lower HbA 1c and at earlier time points posttransplant (24). Taken together, these findings suggest that defective proinsulin processing may be a marker of graft dysfunction and eventual failure and may be exacerbated by hyperglycemia (25).…”
Section: Impaired Proinsulin Processingmentioning
confidence: 98%
“…Interestingly, the proinsulin/ C-peptide ratio is particularly elevated in islet transplant recipients who fail to maintain insulin independence (21)(22)(23), suggesting an association with graft failure. One study reported no difference in proinsulin/insulin ratio among islet transplant recipients, normal control subjects, and immunosuppressed recipients of other organ transplants in patients with lower HbA 1c and at earlier time points posttransplant (24). Taken together, these findings suggest that defective proinsulin processing may be a marker of graft dysfunction and eventual failure and may be exacerbated by hyperglycemia (25).…”
Section: Impaired Proinsulin Processingmentioning
confidence: 98%
“…In addition to impaired glucagon responsiveness, islet engraftment in the liver is also associated with a deficiency of pancreatic polypeptide (PP) release (53); a loss of nutrient-stimulated PP secretion in CP contributes to hepatic insulin resistance. The combined deficiency of glucagon and PP responsiveness in transplanted islets recapitulates the defect seen in other versions of pancreatogenic or type 3c diabetes.…”
Section: Improving Success Of Islet Auto-transplantationmentioning
confidence: 99%
“…Вопросы патогенеза нормальной у реципиентов с трансплантатом почки или сочетанной трансплантацией, которые получали низкую дозу глюкокортикоидов (5 мг ежедневно) и уме-ренную дозу такролимуса (концентрация в крови была в пределах от 6 до 10 мкг/л) [44]. Митохондрии играют ключевую роль в секреции ин-сулина.…”
Section: © сахарный диабет 2015unclassified